2016
DOI: 10.1124/jpet.116.235473
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of the Nitric Oxide Donor Compound 3-(1,3-Dioxoisoindolin-2-yl)Benzyl Nitrate on Dysregulated Phosphodiesterase 5, NADPH Oxidase, and Nitrosative Stress in the Sickle Cell Mouse Penis: Implication for Priapism Treatment

Abstract: Patients with sickle cell disease (SCD) display priapism, and dysregulated nitric oxide (NO) pathway may contribute to this condition. However, current therapies offered for the prevention of priapism in SCD are few. The 3-(1,3-dioxoisoindolin-2-yl)benzyl nitrate (compound 4C) was synthesized through molecular hybridization of hydroxyurea and thalidomide, which displays an NO-donor property. This study aimed to evaluate the effects of compound 4C on functional and molecular alterations of erectile function in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(72 citation statements)
references
References 38 publications
9
55
1
Order By: Relevance
“…Immunoblot analyses with antibodies that selectively recognize P-PDE5A (Ser-92) and PDE5A, respectively, showed that P-PDE5 (Ser-92) and PDE5 protein expressions were significantly reduced (P<0.05) in the penis of vehicle-treated Sickle compared to vehicle-treated WT mice (Fig. 3), consistent with our previous reports (Champion et al 2005, Bivalacqua et al 2007, Lagoda et al 2013, Silva et al 2016). Testosterone treatment of Sickle mice significantly (P<0.05) increased P-PDE5 (Ser-92) and PDE5 protein expressions to levels comparable to WT levels, indicating that testosterone completely normalized downregulated PDE5 activation and protein expression in the Sickle mouse penis.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Immunoblot analyses with antibodies that selectively recognize P-PDE5A (Ser-92) and PDE5A, respectively, showed that P-PDE5 (Ser-92) and PDE5 protein expressions were significantly reduced (P<0.05) in the penis of vehicle-treated Sickle compared to vehicle-treated WT mice (Fig. 3), consistent with our previous reports (Champion et al 2005, Bivalacqua et al 2007, Lagoda et al 2013, Silva et al 2016). Testosterone treatment of Sickle mice significantly (P<0.05) increased P-PDE5 (Ser-92) and PDE5 protein expressions to levels comparable to WT levels, indicating that testosterone completely normalized downregulated PDE5 activation and protein expression in the Sickle mouse penis.…”
Section: Resultssupporting
confidence: 91%
“…2C) and poststimulated ICP/MAP area (Fig. 2D) were significantly (P<0.05) higher in vehicle-treated Sickle compared with vehicle-treated WT mice after cavernous nerve electrical stimulation was terminated, consistent with our previous report (Silva et al 2016). Testosterone completely normalized (P<0.05) detumescence time/MAP and poststimulated ICP/MAP area in Sickle mice, indicating correction of prolonged poststimulation erectile responses in these mice.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations